TOXICITY TEST OF ROSELLE CALYX EXTRACT ON OSTEOBLASTS CELLS USING MTT ASSAY - Pakpahan, Evie Lamtiur (Moestopo International Review on Social, Humanities, and Sciences, 2025)
Background: Roselle calyx are the part of the roselle plant that is most often used as an extract because it has a lot of bioactive content. Roselle calyx contain dietary fiber, polyphenols, vitamin C, iron, zinc, calcium, magnesium, and potassium, often used as raw materials for herbal medicines. Polyphenols as a whole also have benefits for bone remodeling. Polyphenols can maintain bone integrity by reducing oxidative stress, reducing inflammation through signaling pro-inflammatory and modulation of osteoblastogenesis or osteoclastogenesis through osteoimmunological actions. Methods: Cytotoxicity was evaluated using MTT assay, and data were analyzed using the Shapiro-Wilk normality followed by one-way ANOVA and Tukey’s HSD post hoc test. Results: The result showed that osteoblast cell viability after treatment with roselle calyx extract was 93.95% at 15%, 99.60% at 20%, 108.87% at 25%, and a concentration of 30% had the highest cell viability percentage of 136.69%. Conclusion: Roselle calyx extract is non-toxic to osteoblast cells and has the potential as an alternative natural material to inhibit relapse in orthodontic treatment.